The Influence of FOMO and Self-Control on the Academic Concentration of Students of the University of Muhammadiyah Palopo - Aprawati; Hadi Pajarianto; Nur Saqinah Galugu (CV. Era Digital Nusantara, 2026)
This study aims to analyze the influence of fear of missing out (FOMO) and self-control on the academic concentration of students of the University of Muhammadiyah Palopo, both partially and simultaneously. This study uses a quantitative approach with an associative type. The research population amounted to 1,040 students of the Faculty of Teacher Training and Education, with a sample of 91 respondents selected using the proportional stratified random sampling technique. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression with the help of SPSS. The results showed that partially FOMO did not have a significant effect on academic concentration (Sig. = 0.108 > 0.05), which means that FOMO did not directly affect students' ability to maintain focus on learning. In contrast, self-control had a positive and significant effect on academic concentration (Sig. = 0.001 < 0.05), which suggests that the higher the self-control, the better the student's academic concentration. Simultaneously, FOMO and self-control had a significant effect on academic concentration (Sig. = 0.001 < 0.05). The value of the determination coefficient (R²) of 0.794 indicates that 79.4% of the variation in academic concentration can be explained by both variables. In conclusion, self-control is the dominant factor that affects academic concentration, whereas FOMO has no significant direct influence.